Appraising Neonatal Morbidity and Mortality in a Developing Country Categorized by Gestational Age Grouping and Implications for Targeted Interventions - Mokuolu, Olugbenga Ayodeji; Adesiyun, Omotayo Oluwakemi; Ibrahim, Olayinka Rasheed; Suberu, Habibat Dirisu; Ibrahim, Selimat; Bello, Surajudeen Oyeleke; Mokikan, Moboni; Obasa, Temitope Olorunshola; Abdulkadir, Mohammed Baba (Frontiers in Pediatrics, 2022)
Introduction: Despite the relatively higher neonatal morbidity and mortality in developing countries, there are few data on the detailed analysis of the burden in Nigeria. With a database of over 14,000 admissions, this study presents a compelling picture of the current trends disaggregated by their gestational age groups. It provides unique opportunities for better-targeted interventions for further reducing newborn mortality in line with SDG 3, Target 3.2. Methods: This prospective observational study involved newborn babies admitted to the Neonatal Intensive Care Unit of University of Ilorin Teaching Hospital, Kwara State, Nigeria, between January 2007 and December 2018. The outcome was the neonatal mortality rates. The exposure variables considered included birth weight, gestational age (preterm versus term), and clinical diagnosis. Frequencies were generated on tables and charts, and the trends or associations determined. Results: Of the 14,760 neonates admitted, 9,030 (61.2%) were term babies, 4,847 (32.8%) were preterm babies and in 792(5%) of the admissions, the gestational ages could not be determined. Males constituted a larger proportion (55.9%), and deaths in the study period were 14.7%. Mortality was highest among babies with birth weight less than 1000g (38.0%) and gestational age < 28 weeks (65.5%). The trend analysis showed that the mortality rate decreased from 17.8% to 13% over thetwelve-year period, p= <0.0001. For term babies, mortality decreased by 45% from 15.7% in 2007 to 8.7% in 2018 while decline in mortality for preterm babies was 28.4% from 25.7% in 2007 to 18.4% in 2018, p <0.001. Regarding morbidity in term babies, asphyxia occurred in (1:3); jaundice (1:5); sepsis (1:6) and respiratory disorders (1:6) of admissions. For mortality, it was asphyxia in 1:2; sepsis 1:5; jaundice 1:8 and respiratory disorders 1:10 of deaths. Leading causes of morbidity among preterm babies were asphyxia 1:4; sepsis (1:5); respiratory disorders (1:9); and jaundice (1.10). For mortality, their contributions were asphyxia (≈1:2); sepsis (1:5); respiratory disorders (1:9) and jaundice (1:10) Conclusions: There was marked improvement in neonatal mortality trends over the period, however. Severe perinatal asphyxia, sepsis, hyperbilirubinemia and respiratory disorders were the leading conditions contributing to 75% of the morbidities and mortalities.